Estimating firms' bank-switching costs - Karolis Liaudinskas; Kristina Grigaitçe (Norges Bank, 2021)
We explore Lithuanian credit register data and two bank closures to provide a novel estimate of firms' bank-switching costs and a novel identification of the hold-up problem. We show that when a distressed bank's closure forced firms to switch, these firms started borrowing at lower interest rates immediately and permanently. This suggests that firms were held up and overcharged exante, and reveals the lower bound of their ex-ante switching costs. Opaquer firms were overcharged more, which suggests that information asymmetries significantly contribute to switching costs. In line with banks' reputational concerns, a healthy bank's closure revealed no overcharging. To policy-makers, our results suggest potential benefits of distressed banks' closures.
hdl:11250/2758398
Keywords: D82; E51; G21; G33; L14; 330; switching costs; lending relationships; hold-up; asymmetric information; bank closures; financial distress